(untitled) (Research, Society and Development, 2021)
The knowledge of the rainfall regime has great importance for determining the average annual precipitation, mainly for locations where precipitation is intense and with an increasing tendency over the years, as well as for water resource management plans. The main goal of this research was to determine the average annual precipitation in the Metropolitan Region of Belém (MRB), by comparing and verifying the variations between the obtained results. Therefore, three different methods were applied: Arithmetic Mean, Thiessen Polygon and Isohyets (through interpolation by ordinary Kriging and inverse of the square of the distance) for three different data conditions (historical data with: 37, 28 and 20 years). The obtained results, precipitation values around 2,841 mm, shows that the variations were insignificant for Thiessen and Isohyet methods, while the Arithmetic Mean method was distant from the others with an average of 2,604 mm. Finally, it was concluded from the obtained results that even with an irregular distribution of the rainfall stations, that is a very common situation, and a little rugged relief, the Thiessen Polygon and Isohyet methods are equivalent for the objective in question, having no significant variation between these conditions.